Penguatan Partisipasi Masyarakat dalam Pengelolaan Sampah di Kawasan Pantai Peunaga Pasi, Kabupaten Aceh Barat - Mardhatillah, Muntaha; Kahanna, Mutia; Fatimah, Fatia (Universitas Negeri Gorontalo, 2025)
This community service activity was held at Peunaga Pasi Beach, West Aceh Regency, which has great potential as a leading tourist destination, but faces pollution problems due to people's habit of littering. This community service aims to foster active community participation in maintaining the cleanliness of the beach environment through a participatory education approach and technical waste management training. Activities were carried out through initial surveys, socialization, composting training, and the formation of the Peunaga Pasi Bersih Forum community. The evaluation process was carried out through direct observation during the activity to see the real involvement and behavioral changes of residents. The results showed an increase in community understanding by 65% and a reduction in illegal waste by 35%. This activity shows that a community-based approach can build a clean culture that not only beautifies the coastal area, but also strengthens the community's social involvement in protecting the environment in a sustainable manner.